A Comparative Analysis of the Effects of Reduced Positional Games and Traditional Training on the Physical and Technical Performance of Young Soccer Players in Training - Errama, Mostafa; Bassiri, Mustapha; Atifi, Jafaar; Lotfi, Said (Physical Education Theory and Methodology, 2024)
Background. Implementing reduced positional games as a training method in modern soccer has been represented as an important determinant in improving and developing the skills of young soccer players in training. Objectives. The study aimed to determine the effect of a 12-week period of reduced positional games on the physical and technical performance of young soccer players in training. Materials and methods. Forty male soccer players in training of the Moroccan U17 national championship club CFC participated in this study. The players were divided, according to their club, into an experimental group with reduced positional games and a control group engaged in traditional training. Both teams took part in training sessions three times a week for 12 weeks. Each session lasted 90 minutes. Before and after the intervention, both groups performed physical tests (Yo-Yo intermittent test, linear sprint of 10 m, 20 m and 20 m with a change of direction, SJ — Squat Jump, CMJ — Countermovement Jump) and technical tests (LSPT — The Loughborough Soccer Passing Test, LSST — The Loughborough Soccer Shooting Test), all performances achieved by both groups were evaluated. The OptoJump, My Jump application, and technical test grid were used to quantify the results. Results. The results revealed significant improvements in MAS (p < .001; n² = 0.017); 10 m sprint (p < .001; n² = 0.102), 20 m sprint (p = 0.002; n² = 0.022), 20 m sprint (p < .001; n² = 0.022), 20 m sprint with a change of direction (p < .001, n² = 0.087), as well as an increase in height in the SJ (p < .001; n² = 0.012) and CMJ (p < .001; n² = -0.016). Compared to the LSPT results, an increase in the number of passes was observed in the experimental group (p < .001; n² = 0.175) and a notable enhancement in pass control (p < .001; n² = 0.131). The LSST test showed a significant increase in shooting performance (p = .001; n² (right foot) = 0.045; n² (left foot) = 0.049) and a decrease in shooting time (p = .001; n² (right foot) = 0.045, n² (left foot) = 0.005). Post-hoc tests demonstrated that training involving reduced positional games resulted in greater improvements in the SJ, CMJ, 10m sprint, 20m sprint, 20m sprint with a change of direction, LSPT,and LSST. Conclusions. The findings indicate that a 12-week training program based on reduced positional games, incorporating 3 sessions per week, led to a considerable enhancement in the physical and technical performance of young soccer players in training. Therefore, it is recommended to coaches and physical trainers to include training sessions based on reduced positional games into the team’s annual program.